2021
DOI: 10.1080/02640414.2021.1959981
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and effective novel home-based training set-up for application of an evidence-based high-loading stimulus to improve triceps surae function

Abstract: 2021): Reliable and effective novel home-based training set-up for application of an evidence-based high-loading stimulus to improve triceps surae function, Journal of Sports Sciences,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Structural adaptation also does not directly translate into an improvement in function or better performance, even though higher tendon stiffness is reported to contribute to improved jump performance [ 84 ]. While in healthy adults the home-based application of the same high-load protocol led to increased DJ height [ 41 ], in the tendinopathy patients of this study no change in DJ height was observed and the CMJ height even dropped post-intervention. Moreover, while Achilles tendinopathy is said to be accompanied by a decrease in functional capacity such as vertical jumping [ 85 ], a clinically effective exercise therapy that was associated with significant improvements in VISA-A score did similarly not result in improved CMJ performance [ 49 ].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Structural adaptation also does not directly translate into an improvement in function or better performance, even though higher tendon stiffness is reported to contribute to improved jump performance [ 84 ]. While in healthy adults the home-based application of the same high-load protocol led to increased DJ height [ 41 ], in the tendinopathy patients of this study no change in DJ height was observed and the CMJ height even dropped post-intervention. Moreover, while Achilles tendinopathy is said to be accompanied by a decrease in functional capacity such as vertical jumping [ 85 ], a clinically effective exercise therapy that was associated with significant improvements in VISA-A score did similarly not result in improved CMJ performance [ 49 ].…”
Section: Discussionmentioning
confidence: 68%
“…High-load group : Patients in the High-load group obtained a feedback-fitted sling (displaying the applied force due to an integrated strain gauge) for home-based application [ 41 ] of the high-loading protocol reported by Arampatzis et al [ 26 ], which provides an efficient stimulus for tendon adaptation [ 27 , 28 , 46 , 47 ]. Patients were instructed to sit on the floor with extended knees.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, individuals who participate in an exercise activity with an aerial phase should slowly increase their training intensity level to allow the Achilles tendon sufficient time to adapt to the high impact loading. Further, when performing a sport with an aerial phase, it might be helpful to include specific strength training sessions, as proposed recently by Radovanović et al (2021) . Such strategies could help to improve Achilles tendon properties and to prevent overuse injuries.…”
Section: Discussionmentioning
confidence: 99%